Design and fabrication of (Hf0.25Zr0.25Ta0.25Nb0.25)C–SiC ceramics with improved microwave absorbing properties via PDC route - Bin Du; Saidi Wang; Linwei Guo; Yimin Ouyang; Hanwei Cheng; Yajuan Cheng; Tao Zhang (Journal of Advanced Ceramics)
The development of advanced and efficient microwave-absorbing materials through the precise regulation of dielectric loss and impedance matching remains a significant challenge. In this study, (Hf0.25Zr0.25Ta0.25Nb0.25)C–SiC (HEC–SiC) biphasic ceramic powders were synthesized via a single-source-precursor route. The SiC content was systematically controlled by adjusting the amount of methyltrimethoxysilane. The resulting polymer-derived HEC–SiC composite exhibited a unique microstructure, with nanosized SiC particles uniformly distributed throughout the HEC matrix. As a result, the HEC–SiC-2 composite, containing approximately 21.21 wt% SiC, achieved a minimum reflection loss value (RLmin) of −54.28 dB at 12.39 GHz with a thickness of 3.14 mm. The superior microwave attenuation capability is attributed to optimized impedance matching, enhanced interfacial polarization between the HEC matrix and nanosized SiC, and dipole polarization induced by defects within HEC. This study offers a novel strategy for the fabrication of high-entropy ceramic–SiC biphasic composites with excellent microwave absorbing properties, paving the way for their application in electromagnetic interference shielding and stealth technologies.